Preparing for Korean unification : scenarios and implications - Pollack, Jonathan D. (RAND, 1999)
This study examines four alternative scenarios that would result in the unification of the Korean peninsula. The authors describe the defining characteristics of each scenario, potential indicators that would predict specific outcomes, some possible variations in paths to unification, and some operational implications for the U.S. Army under different conditions and circumstances. The four scenarios (peaceful unification, collapse and absorption, unification through armed conflict, and disequilibrium and external intervention) highlight both the increasing vulnerabilities of the North Korean state and the substantial uncertainties that attach to each outcome and to the potential U.S. policy responses. These considerations impose major conceptual, policy, and operational challenges both in the near and middle term and in the postunification peninsular security environment. Each warrants an enhanced analysis and assessment effort, lest U.S. and ROK policymakers find themselves ill prepared for major challenges to alliance management and to the U.S. Army role in a future crisis.